Towards a Caribou Habitat Management Strategy for Northwestern Ontario: Running the Gauntlet - Racey, Gerald D.; Armstrong, Edward R. (Rangifer, 1996)
A management strategy for woodland caribou (Rangifer tarandus caribou) habitat is being developed in northwestern Ontario. This strategy is based upon a set of draft Timber Management Guidelines for the Provision of Woodland Caribou Habitat. These guidelines recommend maintaining a sustainable supply of winter habitat within large tracts of old forest, protecting calving areas and minimizing human disturbance. Due to the large temporal and spatial scale of caribou habitat management, an ecosystem-based approach is recommended. Public response to the strategy shows a strong dichotomy between environmental and utilitarian values among all the major stakeholder groups. The major issues raised by the public include security of industrial wood supply, quality of the knowledge base, level of awareness of caribou, economic impacts on remote communities, concern about environmental impacts and silvicultural know-how. The government is responding to these concerns as the strategy evolves. Current emphasis is placed on increasing awareness of the public, training resource managers in caribou biology, management and habitat planning, implementing interim habitat management prescriptions and studying the potential impact on wood supply. The final direction for a northwestern Ontario strategy to conserve woodland caribou habitat has yet to be decided, although a commitment has been made to strive for the conservation of woodland caribou populations and their habitat.